Analysis of The Effect of Plyometric Training on Improving Three-Point Shooting Ability in Basketball - Raihan Auzora Putra; Hidayah, Taufiq (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
One of the common problems among high school basketball players is the lack of balance and consistency when performing three point shots, which negatively affects scoring performance. This research seeks to examine the influence of plyometric training specifically depth jump and box jump drills for enhancing three-point shooting skill. A semi-experimental approach employing a single-group pre-evaluation-post-evaluation was applied to a sample of 15 male students from SMA Santo Paulus, Jakarta. The training intervention lasted five weeks, with 14 sessions conducted three times per week. Shooting performance was measured from five standard angles on the three-point arc, and data were analyzed using Shapiro-Wilk, Levene’s test, and paired sample t-test. The results showed a significant improvement in three-point shooting scores after the intervention (t = -4.356; p = 0.000), indicating that plyometric training enhances lower-body strength, balance, and shooting accuracy. It can be concluded that structured plyometric exercises contribute positively to three-point shooting performance in basketball athletes.